Silage from water hyacinth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Water hyacinth can be made into a palatable cattle feed if ensiled with paddy straw, molasses and urea. Trials at the Indian Veterinary Research Institute have shown that such silage can meet the protein requirements of animals but more energy...